Aktor Penting dalam Ekosistem Kewirausahaan Pertanian Hortikultura di Jawa Barat: Dilihat Dari Perspektif Teori Jaringan - Mukti, Gema Wibawa; Charina, Anne; Kusumo, Rani Andriani Budi (Universitas Galuh, 2024)
This paper aims to find out the actors that play the most role in the entrepreneurial ecosystem of young farmers in West Java. The analysis tool used is centrality analysis based on network theory, using the Gephi 9.2 application. Informants and respondents in this study consisted of actors involved in the entrepreneurial ecosystem of young farmers, including young farmers, government, financial institutions, universities, markets and social communities. The determination of informants is determined purposively, namely by looking at their role and involvement in the business process of young horticultural farmers, spread across Garut Regency, Cianjur Regency and Bandung Regency, West Java. Indicators of the degree of centrality, centrality of proximity, centrality of intermediaries and Eigencentrality, show that social societies are actors that consistently interact and connect a lot with young farmers. The social community acts as a liaison actor between young farmers and other agricultural stakeholders, always providing positive motivation and encouragement for farmers in agricultural activities. Social community actors must remain involved in horticultural agribusiness in West Java, especially champion farmers, community leaders and agricultural communities. Social community actors not only provide support in the aspects of labor and social capital, but become important actors in creating a conducive and productive farming climate, thus becoming an attraction for the younger generation of agriculture.